Marketing Management / Strategies and Programs - Guiltinan P. Joseph; Paul W. Gordon (Mcgraw Hill Book Company, 1988)
Preface, Managerial Perspectives on Marketing, Corporate Marketing Planning, Situation Analysis, Market Mesurement, Marketing Strategies and Programs, Product-Development Programs, International Marketing Strategies and Programs, Coordination and Control, The Annual Marketing Plan, Index.
Preface, Managerial Perspectives on Marketing, Corporate Marketing Planning, Situation Analysis, Market Mesurement, Marketing Strategies and Programs, Product-Development Programs, International Marketing Strategies and Programs, Coordination and Control, The Annual Marketing Plan, Index.